Analisis Peran Keluarga dalam Mendorong Motivasi Belajar Anak di Tingkat Sekolah Dasar Negeri Badalungga Kecamatan Awayan Kabupaten Balangan - Ubaidillah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This research is motivated by the importance of the family's role in enhancing children's learning motivation at the elementary school level, particularly at Badalungga State Elementary School. Students' learning motivation varies, ranging from high to low, indicating the influence of the family environment on children's enthusiasm for learning. As the primary educational environment, the family is responsible for providing attention, guidance, and moral support to children to foster strong learning motivation. Therefore, this study aims to determine the role of the family in fostering children's learning motivation at the elementary school level. The research method used was a descriptive qualitative approach. Data collection techniques included interviews, observation, and documentation. Informants in this study included teachers, students, and parents. Data were analyzed through data reduction, data presentation, and conclusion drawing to obtain an in-depth understanding of the family's role in student learning motivation. The results show that the family plays a significant role in enhancing children's learning motivation. Children who receive attention, guidance, and support from their parents tend to have higher learning motivation, are more disciplined, and are more active in learning. Conversely, a lack of family involvement can lead to low student learning motivation. Thus, it can be concluded that the family plays a crucial role in encouraging children's learning motivation at Badalungga Public Elementary School.